Cardiac effects of echinocandin preparations – three case reports. (2nd July 2013) - Lichtenstern, C.; Wolff, M.; Arens, C.; Klie, F.; Majeed, R. W.; Henrich, M.; Uhle, F.; Weiterer, S.; Röhrig, R.; Weigand, M. A.
Summary: What is known and objective: Echinocandins are antifungal agents, routinely used in invasive candida infections in critically ill patients. Their excellent anticandidal activity and their low frequency of reported adverse events and drug interactions make them first‐line guideline treatments of candidiasis especially in intensive care units (ICU). We report on three ICU patients who developed cardiac insufficiency and hemodynamic instability during administration of loading doses of an echinocandin. Case summary: Three ICU patients showed a substantial drop in their cardiac index or a deterioration of the mean arterial pressure following start of echinocandin administration. The patients were 75 years (female), 71 years (male) and 66 years (male) old. One patient received caspofungin, and two patients received anidulafungin as empirical antifungal treatment for severe sepsis. What is new and conclusion: Our cases suggest that the observed cardiac impairment could be associated with echinocandin administration. Therefore, we recommend close hemodynamic monitoring of critically ill patients receiving echinocandins.